A metric focused performance assessment of fog computing environments: A critical review. (October 2022) - Rathi, Sugandha; Nagpal, Renuka; Mehrotra, Deepti; Srivastava, Gautam
Abstract: The usage of connected Internet of Things (IoT) devices has increased exponentially. The data generated from these devices is used for real-time analysis to address real-world problems after processing with the help of fog servers. Various metrics are proposed in the literature to access fog servers' performance. This paper presents a detailed review of papers focusing on fog computing metrics like offloading, resource management, QoS, and privacy & security with their parameters such as latency, execution time, makespan, etc. Fog metrics are classified as general metrics and green IoT metrics, which affect the performance of fog environments in multiple ways. The critical analysis highlights the dependency of fog environments on multiple parameters and a trade-off between these parameters is necessary while creating an optimized environment. This paper explores the tools used and optimized parameters and limitations for deeper insight. The analysis is extended for the applicability of fog environments in different application areas and future directions.